(untitled) (Revista Internacional de Folkcomunicação, 2022)
The present study analyzes intersections between Organizational Communication and Folkmarketing through historical elements of the formation of a construct focused on the communicational role as a relevant factor for organizations in the image aspect. In view of this, the path taken by this field is exposed not only in Brazil, but also in the United States, a country that is one of the precursors in this practice. The evolution of Organizational Communication in the country in the final years of the Military Regime is incisively demonstrated, as well as the new consumer behavior of that time. The role played by Folkmarketing and its integration with elements of the field that involves communication in organizations is raised with emphasis, leaving evidence at the end of the work, the decisive role of Folkmarketing as an effective and affective strategy with the consumer public increasingly aware and demanding in the current scenario of the Information Society.